Pathologic anatomy of the soft palate, part 1: Embryology, the hard tissue platform, and evolution - Michael H Carstens (Wolters Kluwer Medknow Publications, 2017)
The purpose of this communication is to explore in detail the developmental anatomy of the soft palate, its pathologies, and strategies for management. Despite the voluminous literature regarding complete cleft palate in its usual presentation, little attention has been paid to the biology of the isolated soft palate cleft. It exists as a spectrum, ranging in severity from the submucous variant, with nothing notable save a groove and a palpable defect of the posterior spine, all the way to a complete disruption of the soft tissue envelope and the horizontal palatine shelves. All these presentations are but variations of common pathology. Much can be gained from a disciplined examination of these. Our discussion includes two parts. The first part is on the embryologic events that generate the mesenchymal building blocks from which the posterior palate is constructed: palatine bone, oral and nasal mucosa, palatine aponeurosis, and muscle slings. Palate structures develop from neural crest and mesoderm; these tissues originate at specific sites along the axis of the embryo and they can be mapped according to the developmental units of the central nervous system (CNS) from which they are innervated. These units, called neuromeres, are specific zones within the neural tube, the boundaries of which are established by the expression pattern of homeotic genes. The forebrain (prosencephalon) has telencephalon and 3 prosomeres, the midbrain (mesencephalon) has 1-2 mesomeres, and the hindbrain (rhombencephalon) has 12 rhombomeres. Each neuromere has a specific neuroanatomic content and is hardwired to specific tissues outside the brain. We next consider a model of the palate which is analogous to a pinball machine that consists of a platform (bone) and mobile "flippers" or lever arms (the velum). In this study, the osseous platform is discussed in detail with neural crest bones being coded by the sensory innervation of their surrounding soft-tissue envelope. Maxilla, palatine bone, and vomers are all derivatives of hindbrain neural crest arising from rhombomere 2 but distributed according to various neurovascular pedicles of the V2 stapedial system, the anatomy of which will be explained in detail. Next, the evolution of palate will be presented as a series of innovations favoring increased metabolic capacity. A final appendix presents a functional classification of cranial nerves which I have endeavored to make straightforward. This will prove useful when reading the second part of this manuscript having to do with the neuromuscular apparatus of the soft palate.